Early Triassic super-greenhouse climate driven by vegetation collapse - Zhen Xu; Jianxin Yu; Hongfu Yin; Andrew S. Merdith; Jason Hilton; Bethany J. Allen; Khushboo Gurung; Paul B. Wignall; Alexander M. Dunhill; Jun Shen; David Schwartzman; Yves Goddéris; et al. (Nature Communications)
Abstract The Permian–Triassic Mass Extinction (PTME), the most severe crisis of the Phanerozoic, has been attributed to intense global warming triggered by Siberian Traps volcanism. However, it remains unclear why super-greenhouse conditions persisted for around five million years after the volcanic episode, with one possibility being that the slow recovery of plants limited carbon sequestration. Here we use fossil occurrences and lithological indicators of climate to reconstruct spatio-temporal maps of plant productivity changes through the PTME and employ climate-biogeochemical modelling to investigate the Early Triassic super-greenhouse. Our reconstructions show that terrestrial vegetation loss during the PTME, especially in tropical regions, resulted in an Earth system with low levels of organic carbon sequestration and restricted chemical weathering, resulting in prolonged high CO2 levels. These results support the idea that thresholds exist in the climate-carbon system whereby warming can be amplified by vegetation collapse.